Pengaruh Pijat Oksitosin Terhadap Produksi ASI Pada Ibu Post Partum - Pipit Feriani; Regina Nur Azizah; Herdianti Herdianti; Nadya Indah Sari; Gusnawati Sulaeman; Afifah Anwar (Pusat Riset dan Inovasi Nasional, 2025)
Oxytocin massage is a non-pharmacological intervention proven effective in increasing breast milk production in postpartum mothers. This technique involves gentle massage along the spine to stimulate the release of oxytocin, a hormone involved in the let-down reflex and milk ejection. A review of multiple studies shows that oxytocin massage significantly enhances both the volume of breast milk and breastfeeding frequency. The intervention also provides relaxation benefits, reducing stress in breastfeeding mothers. Therefore, oxytocin massage is recommended as part of maternal nursing practices to support the success of exclusive breastfeeding.